A BCG hydrogel enables localized NOD2/STING activation to overcome resistance to immune checkpoint blockade - Ziyuan Xiao; Huizhen Xu; Ningyi Ma; Lei Lei; Chunyu Cong; Ningyi Sun; Guodong Wang; Xingmei Chen; Ke Ren; Haishi Qiao (Proceedings of the National Academy of Sciences, 2026)
Resistance to immune checkpoint blockade (ICB) often arises from immunologically cold tumors enriched in suppressive myeloid cells. Previous studies have implicated NOD2 signaling in antitumor immunity and in modulation of ICB responses, but approaches to engage this pathway effectively and durably within tumors remain limited. Here, single-cell transcriptomic analysis of colorectal cancer identified a NOD2 high tumor-associated macrophage (TAM) subset enriched for inflammatory and immune-activating programs. To therapeutically harness this state, we engineered an injectable manganese-containing alginate hydrogel encapsulating polyarginine-functionalized Bacillus Calmette-Guérin (MHY@PBCG) for sustained intratumoral delivery and localized coactivation of NOD2 and STING signaling in TAMs. Polyarginine enhanced BCG uptake by macrophages, whereas Mn 2+ stabilized the hydrogel and amplified STING activation. Local administration of MHY@PBCG reprogrammed TAMs toward an M1-like phenotype, increased inflammatory cytokine and interferon programs, converted cold tumors into immune-inflamed lesions, and restored responsiveness to anti-PD1 therapy in multiple models. Mechanistically, coordinated NOD2/STING activation established a self-reinforcing inflammatory circuit linking macrophage reprogramming to downstream T cell–mediated antitumor immunity. These findings establish a localized biomaterial strategy for overcoming checkpoint resistance through macrophage-centered remodeling of the tumor microenvironment.